2014
DOI: 10.7585/kjps.2014.18.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Phytotoxic by Adjusted pH and Control effect of Loess-Sulfur Complex as Organic Farming Material against Powdery Mildew in Tomato

Abstract: The soluble loess-sulfur mixture allowed standing to remove insoluble component materials for five weeks after manufacturing. We decreased the pH level of soluble loess-sulfur mixture at pH 1.0 modified with decreasing 25% sodium hydroxide than original content. The pH ranges of soluble loess-sulfur mixture solutions were adjusted to pH 5.0-pH 11.0 (pH 1 unit) with brown rice vinegar (pH 2.8). The pH of original loess-sulfur mixture was about pH 13 and damaged the foliar parts and young leaves of tomato after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The occurrence of skin sooty dapple disease on Asian pear is decreased by treatment with lime-sulfur [18]. On tomato leaves sprayed with loess-sulfur, the occurrence of tomato powdery mildew is decreased [19]. Also, lime- or loess-sulfur has been used to prevent anthracnose by Colletotrichum gloeosporioides or circular leaf disease by Mycosphaerella nawae on sweet persimmon, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of skin sooty dapple disease on Asian pear is decreased by treatment with lime-sulfur [18]. On tomato leaves sprayed with loess-sulfur, the occurrence of tomato powdery mildew is decreased [19]. Also, lime- or loess-sulfur has been used to prevent anthracnose by Colletotrichum gloeosporioides or circular leaf disease by Mycosphaerella nawae on sweet persimmon, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that disease severity of powdery mildew is decreased by about 90% in tomato plants treated with loess-sulfur mixture (Shim et al, 2014). Ginseng anthracnose caused by Colletotrichum gloeosporioides is also suppressed by treatment with lime sulfur diluted 400 times (Lim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…살균제로서 유황은 1800년대 프랑스에서 포도 흰가루병으로 인하여 포도주 생산량의 80%까지 감소하면서 포도 흰가루병을 방제하기 위하여 본격적으로 사용되기 시작하였고 (Shim et al, 2014;Tiecher et al, 2017), 1845년 미국 으로 전해져 포도과원에 흰가루병 뿐만 아니라 응애에도 방제효과가 있어 광범위하게 사용되게 되었다 (Buchanan and Amos, 1992;Emmett et al, 1992). 유황은 유기농업자재로서 미국, 유럽, 우리나라 등지에서 사용이 허용되어 있 다 (Ahn, 2010;EPA, 1991;OMRI 2012 Organic matter (g kg …”
Section: Application Rateunclassified